2022
DOI: 10.36416/1806-3756/e20220153
|View full text |Cite
|
Sign up to set email alerts
|

Casassola GM, Schmidt CJ, Affeldt G, Morais DS, Alvarenga LKB, Miller C, Ziegler B Functional status of hospitalized pediatric patients with COVID-19 in southern Brazil: a prospective cohort study

Abstract: Objective: The present study aimed to assess the functional status of children diagnosed with COVID-19 at the time of hospitalization and the associations with clinical features. Methods: This prospective cohort study was carried out with children diagnosed with COVID-19 admitted to a tertiary hospital. The patients' functioning was assessed using the pediatric Functional Status Scale (FSS). Results: A total of 62 children with a median age of 3 years old were included in the study, and 70% had some comorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
1
0
2
Order By: Relevance
“…Casassola et al demonstrated that over half of children hospitalized with COVID-19 have impaired functionality, which they found to be associated with a longer hospital stay and a greater likelihood of requiring ventilatory support. 26 Their findings suggest that pediatric patients with reduced functionality tend to develop the more severe forms of COVID-19 and that one-year mortality rates would therefore be higher among such patients, thus corroborating our findings.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Casassola et al demonstrated that over half of children hospitalized with COVID-19 have impaired functionality, which they found to be associated with a longer hospital stay and a greater likelihood of requiring ventilatory support. 26 Their findings suggest that pediatric patients with reduced functionality tend to develop the more severe forms of COVID-19 and that one-year mortality rates would therefore be higher among such patients, thus corroborating our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Similar data can be found in the literature. 17 , 26 Most of the children hospitalized with COVID-19 have preexisting comorbidities. 7 , 10 , 11 The presence of comorbidities is considered a risk factor for the development of more severe COVID-19 and for unfavorable outcomes such as death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations